Histoprotective potentials of ethanol leaf extract of balakat tree (Ziziphus talanai (blanco) merr.) against tetracycline-induced hepatotoxicity and reprotoxicity in male mice (Mus musculus L.) - Reyes, Angelico; dela Pena, Renato; Sula, Lourdes Fatima; Banares, Angelo (International Journal of Pharmacology and Toxicology, 2016)
Hepatic dysfunction can develop due to ROS and lipid peroxide and may lead to primary liver cancer. Hepatic dysfunction may also develop from tetracycline, an antibiotic with a broad-spectrum of bacteriostatic mechanisms, as it can induce hepatotoxicity and reprotoxicity. In addition, liver tumors secrete hormones that can result to testicular atrophy. Thus, there is a need to address liver and testicular damage. Preliminary phytochemical analysis indicated the presence of bioactive compounds with histoprotective potentials in Balakat tree (Ziziphus talanai), which is used in Antique against urinary tract infection. Twelve male mice were divided into four groups of three mice each. Treatments were administered via intragastric gavage technique for 30 days. T0 is the negative control group treated only with water at a dose level of 0.5 ml/20 g body weight (bw). T+ is the positive control group treated only with tetracycline at a dosage level of 0.5ml/20 g bw. T1 and T2 received 0.3 ml/20 g bw and 0.5 ml/20 g bw Z. talanai ethanol leaf extract, respectively.Histopathological evaluation revealed that T+ mice showed hepatotoxicity based on central vein rupture, fibrosis, vacuolations, cytoplasmic degeneration, lymphocyte infiltration, small amount of glycogen deposits and fibrous septa. Reprotoxicity was also observed as indicated by formation of irregularly shaped tubules, narrowing of tubule diameter, widening of the lumen, germinal epithelium exfoliation, reduction in tubules’ cross-sectional areas, absence of germ cell bundles and blood-testis barrier destruction. T1 and T2 mice showed normal liver and seminiferous tubule architectural design as compared to those of T+ mice. Thus, the Z. talanai leaf extract mitigated the hepatotoxicity and reprotoxicity effects of tetracycline causing an improvement in the hepatological and testicular parameters. The ethanolic leaf extract of Z. talanai (Blanco) Merr. Contains bioactive compounds with histoprotective potentials.